APLIKASI PUPUK ORGANIK CAIR SUMBER NITROGEN DAN INTERVAL PEMBERIAN AIR PADA PERTUMBUHAN DAN HASIL TANAMAN SELADA MERAH : APLICATION OF LIQUID ORGANIC FERTELIZER NITROGEN SOURCE AND WATERING INTERVAL ON THE GROWTH AND YIELD OF RED LETTUCE PLANTS - Mooy, Lenny; Walunguru, Lena; K. Remitana , Yunus; Ginting , Theresia (Fakultas Pertanian Universitas Palangka Raya, 2024)
The growth and produce of red lettuce are influenced by plant growth factors such as the availability of nutrients and water content in planting medium. This study aims to determine the growth and produce of red lettuce by using liquid organic fertilizer and watering intervals. This research employed Randomized Block Design (RBD) Factorial consisting of 12 combinations of treatments and 3 replications with the first factor tested was liquid organic fertilizer consisting of 4 levels namely: without organic liquid fertilizer; Liquid organic fertilizer from tofu pulp; liquid organic from chicken manure; and liquid organic fertilizer from lamtoro leaf. The second factor was the interval of watering: interval 1, 2, and 3 days. The parameters observed were plant height, leaf chlorophyll, wet weight, and dry weight. The results showed that the organic fertilizer treatment of tofu dregs gave the best result of plant height at 2 weeks after planting (WAP) (14.71 cm), 3 WAP (18.19 cm), 4 WAP (23.11 cm), leaf chlorophyll (21.89 mg l-1), wet weight (0.175 g), and dry weight (0.037 g). The treatment of once a day watering interval gave the best result of plant height 2 WAP (15.04 cm), 3 WAP (18.73 cm), 4 WAP (24.17 cm), leaf chlorophyll (20.68 mg l-1), Wet weight (0.183 g), dry weight (0.0038 g), while watering interval once every 3 days gave the highest water efficiency (0.026), and the treatment of liquid organic fertilizer of tofu and once a day watering interval gave the highest wet weight (0.189 g).